Leveraging Design of Experiments to Unravel the Amplification Mechanism of Single‐Molecule Wide‐Field Biosensors - Michele Catacchio; Mariapia Caputo; Lucia Sarcina; Cinzia Di Franco; Matteo Piscitelli; Erika Castrignanò; Paolo Bollella; Gaetano Scamarcio; Eleonora Macchia; Luisa Torsi (Advanced Materials Interfaces, 2025)
Abstract Detecting single molecules on large interfaces, spanning several square micrometers, is often considered unfeasible due to the minimal perturbation individual molecules exert on the sensing surface. However, biological systems, such as cellular membranes, demonstrate remarkable sensitivity, achieving single‐molecule detection on interfaces as large as 103 µm2, despite the stark mismatch between molecular footprints and surface areas. While these amplification mechanisms are well‐documented, their molecular and biophysical foundations remain poorly understood. To contribute to probing these phenomena, a Design of Experiments (DoE) approach explores how pH and ionic strength in conditioning solutions influence Surface Plasmon Resonance (SPR) detection in the single‐molecule regime. Conditioning a physisorbed layer of capturing antibodies at low pH emerges as the key strategy, enabling the reliable detection of only 6 ± 2 IgG molecules with a significant SPR signal. The analysis further reveals that pH conditioning induces a refractive index shift within the antibody layer, which is quantitatively correlated with changes in zeta potential (ζ‐potential). These findings provide critical insights into the mechanisms driving ultrasensitive SPR detection and establish a data‐driven framework for advancing biosensing technologies.